Analisis Tingkat Literasi Wakaf Uang Mahasiswa Fakultas Ekonomi Universitas Negeri Surabaya - Machmud, Aqidatul Izzah; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2020)
There are no institutions that utilize the potential of cash waqf make this study aimed to determine the literacy level of the students Economics Faculty, State University of Surabaya regarding cash waqf. so that stakeholders can take advantage of the cash waqf potential in Economics Faculty, State University of Surabaya. The method used in this researched was descriptive qualitative. The results of this study indicated that in majority at the Faculty of Economics, State University of Surabaya, have a very minimal level of literacy or understanding. The results of the research can provide a picture for stakeholders about the conditions in the environment. Furthermore, only students majoring in Islamic Eonomics who had knowledge above the average of other majors students but were still classified into low levels because the knowledge of the students majoring in Islamic Economics was only limited to basic knowledge.